Enhancing Supercapacitor Performance with Chemically Synthesised RGO/CeO2/PEDOT Nanocomposite - Lakshmipathy, Jayanthi (My University, 2025)
Supercapacitors exhibit exceptional power density, rapid charging and discharging capabilities, and long-term cycling stability, making them promising candidates for energy storage solutions; nonetheless, their electrochemical efficiency is profoundly influenced by the choice and design of electrode materials.1 The creation and characterization of high-performance nanocomposite electrode material for supercapacitor applications are examined in this thesis, focusing on the combination of reduced graphene oxide (RGO) which offers high conductivity and huge surface area, cerium oxide (CeO2) provides redox-active sites, and poly(3,4-ethylenedioxythiophene) (PEDOT) enhances conductivity and pseudocapacitance. RGO/CeO₂ and RGO/CeO₂/PEDOT nanocomposites were synthesised using in-situ oxidation-reduction technique and chemical polymerization method. The prepared RGO, RGO/CeO2 and RGO/CeO₂/PEDOT nanocomposites were thoroughly characterised by using UV-visible spectroscopy, Raman spectroscopy, and XPS. The electrochemical behaviour of fabricated supercapacitors was examined through cyclic voltammetry (CV) and galvanostatic charge-discharge (GCD) techniques using a three-electrode cell setup under 0.5 M H2SO4 electrolyte. The RGO/CeO₂/PEDOT supercapacitor demonstrated greater energy and power densities, as well as a much higher specific capacitance of 150 F/g at a current density of 0.4 A/g as compared to individual RGO and RGO/CeO2 composite. These findings highlight the synergistic effect of combining conducting polymers, metal oxides, and carbon materials, and they show the potential of the RGO/CeO₂/PEDOT nanocomposite as an efficient electrode material for next generation supercapacitors.
Keywords: Reduced graphene oxide, cerium oxide, PEDOT, supercapacitor